A Highly Sensitive UV–vis–NIR All‐Inorganic Perovskite Quantum Dot Phototransistor Based on a Layered Heterojunction. Issue 14 (6th May 2018) - Zou, Chen; Xi, Yuyin; Huang, Chun‐Ying; Keeler, Ethan G.; Feng, Tianyu; Zhu, Shihao; Pozzo, Lilo D.; Lin, Lih Y.
Abstract: All‐inorganic perovskite quantum dots (IPQDs) are a promising material for use in various optoelectronic devices due to their excellent optoelectronic properties and high environmental stability. Here, a high‐performance phototransistor based on a layered heterojunction composed of CsPbI3 QDs and a narrow‐bandgap conjugated polymer DPP‐DTT is reported, which shows a high responsivity of 110 A W −1, a specific detectivity of 2.9 × 10 13 Jones and a light to dark current ratio up to 6 × 10 3 . The heterojunction phototransistor exhibits unipolar p‐type and gate bias modulated behaviors. In addition, the device exhibits a broad spectral detection range from ultraviolet to near infrared. The high sensitivity of the device is attributed to the layered heterojunction and the gate bias modulation property. The work overcomes the existing limitations in sensitivity of IPQD photodetectors due to the poor charge transport between QDs. The convenient solution‐processed fabrication and excellent device performance especially suggest the IPQD/narrow‐bandgap conjugate polymer heterojunction as a promising structure for potential applications of ultrasensitive broadband photodetectors compatible with a wide variety of substrates. Abstract : A UV–vis–NIR phototransistor based on a layered heterojunction composed of CsPbI3 nanocrystals and DPP‐DTT is reported. Thanks to the heterostructure strategy and gate modulation property, the phototransistor exhibits excellent optoelectronic properties. The UV–vis–NIR broadband detection also encourages a broader range of applications. Moreover, the device could almost maintain its performance after being stored in air for 1 month.